Enemy of the state eaudiobook - Flynn, Vince (Mitch Rapp, 2017)
"In the world of black-op thrillers, Mitch Rapp continues to be among the best of the best" ( Booklist , starred review), and he returns in the #1 New York Times bestselling series alone and targeted by a country that is supposed to be one of America's closest allies. After 9/11, the United States made one of the most secretive and dangerous deals in its history—the evidence against the powerful Saudis who coordinated the attack would be buried and in return, King Faisal would promise to keep the oil flowing and deal with the conspirators in his midst. But when the king's own nephew is discovered funding ISIS, the furious President gives Rapp his next mission: he must find out more about the high-level Saudis involved in the scheme and kill them. The catch? Rapp will get no support from the United States. Forced to make a decision that will change his life forever, Rapp quits the CIA and assembles a group of independent contractors to help him complete the mission. They've barely begun unraveling the connections between the Saudi government and ISIS when the brilliant new head of the intelligence directorate discovers their efforts. With Rapp getting too close, he threatens to go public with the details of the post-9/11 agreement between the two countries. Facing an international incident that could end his political career, the President orders America's intelligence agencies to join the Saudis' effort to hunt the former CIA man down. Rapp, supported only by a team of mercenaries with dubious allegiances, finds himself at the center of the most elaborate manhunt in history. With white-knuckled twists and turns leading to "an explosive climax" ( Publishers Weekly ), Enemy of the State is an unputdownable thrill ride that will keep you guessing until the final page.